A landscape analysis of clinical trials and infant clinical trials in Kenya, Ethiopia, and Nigeria - Amboka, Patrick; Kurui, Daniel; Wamukoya, Marylene; Sindi, Julius Kirimi; Vicente-Crespo, Marta (Frontiers in Epidemiology (Online), 2024)
Global inequality in clinical research capacity and service delivery can be indicated simply by the proportion of clinical trials that a country or region has registered in clinical trial registry databases. The proportion of clinical trials registered in Africa is very low at 0.02%, even though the region accounts for approximately 15% of the world's population. Despite the economic challenges in most African countries, they have shown potential for growth and change in recent years. We conducted desk reviews on the interventional clinical trials done in Kenya, Ethiopia, and Nigeria between 2015 to May 2023. The search was done in clinical trials repositories, and journal repositories. The search focused on intervention clinical trials. Data was extracted by screening through the publications and clinical trial platforms. The data extracted from the publications included the type of clinical trial, clinical trial phase, diseases, etc. The data extracted from the reports included: challenges in conducting clinical trials, capacity-building efforts, and the impact of the clinical trial. The number of clinical trial studies identified in Kenya was 113 (28 were on infant clinical trials). The study identified 97 clinical trials in Nigeria, of which 11 studies were on infant clinical trials. In Ethiopia, there were 28 clinical trials and only five were on infant clinical trials. The landscape review also expanded to capacity and gaps in clinical trials in the three countries. The largest proportion of clinical trials carried out in Kenya was on injury, occupational disease, and poisoning, 30.5% ( = 18) and the smallest proportion was on kidney disease, neonatal disease, obstetrics, and gynecology. Most Infant clinical trials were carried out in the area of infections and infestations 33.3% ( = 7). Most of the challenges faced by clinical trials in the three countries include a lack of infrastructure, a lack of human resources, and a lack of financial resources. There is a need to map clinical trials done by African researchers based in Africa to exclude the trials done by non-African researchers based in Africa. Opportunities for clinical trials should be supported and challenges addressed.